Perception of health beliefs and the spread of Tuberculosis (TB) in the Mokopane Area, Mogalakwena Municipality - Mashishi, Lesiba Peter (My University, 2021)
This study was prompted by the number of people who die daily from tuberculosis (TB) in the study area. The study investigated the perceptions of Mokopane residents, and their level of understanding and knowledge of the disease, tuberculosis (TB). The aim of the study was to profile people’s perceptions of health beliefs, the causes of the increase and spread of TB and its prevention and their knowledge about TB awareness campaigns in the Mokopane area. Data was collected by means of both qualitative and quantitative methods. Ten (10) medical doctors who operate private practices in the Mokopane area were interviewed. Data was collected from four hundred and one (401) participants from both Sandsloot and Tshamahansi villages outside Mokopane. The major findings of this study showed that firstly residents have a firm belief that traditional methods cure TB; secondly, they are largely ignorant of TB, its prevention, and consequences; and lastly that there is a lack of TB related education.
Thesis (M. A. (Communication Studies)) -- University if Limpopo, 2021
Keywords: Tuberculosis (TB); Health Communication Messages and beliefs; Tuberculosis -- Prevention; Tuberculosis -- Patients; Tuberculosis -- Alternative treatment